Technological Adoption For The Online System of Public Aspirations and Complaints Service (Lapor) in Bandung City - Helga Meizhura; Dini Turipanam Alamanda; Fajar Sidiq Adi (AFEBI Management and Business Review, 2017)
The city government of Bandung has made serious efforts in solving the urban problems creatively through the utilization of ICT, known as Smart City. One of the smart government programs being implemented is the online public aspirations and complaints service through an application system called LAPOR. So far, the application is considered effective enough to engage public participation, eventhough there are also many contradictory and negative comments shared by the users. Therefore, it is important to find out the actual description of public acceptances for the LAPOR system.The affecting factors of interest and behavior in using the system were identified by the model of UTAUT 2 developed by Venkatesh et al. In 2012. The data in this study was collected using questionnaires distributed to 405 respondents of those who live in Bandung city, either the users of LAPOR application or those who have not used it yet. The results showed that the most influential factor of interest in using the LAPOR system is Price Value. This indicates that public wants the proportional benefits of the costs incurred for using the system.Other influential factors are Hedonic Motivation, Social Influence, Habit, and Facilitating Condition. Hence, these findings will enable practitioners to gain information in improving the successful implementation of technology-based governance programs. Keywords: Smart City, Smart Government, UTAUT 2